Weak scale supersymmetry : from superfields to scattering events - Baer, Howard (Cambridge University Press, 2006)
A comprehensive, practical and accessible introduction to supersymmetry for particle physicists. It develops the concepts of supersymmetry into a framework for describing unified theories of elementary particles. It leads to a straightforward recipe for writing supersymmetric gauge theories and the calculations necessary for practical applications at colliders and in cosmology.